Quantitative profiling of bacteriocin present in dairy probiotics preparation of Lactobacillus pentosus by liquid chromatography mass spectrometery - Verma, Garima; Virk , Verinder (Journal of Postharvest Technology, 2022)
Bacteriocins are a heterogeneous group of ribosomally synthesized peptides or proteins with antimicrobial activity, produced predominantly by lactic acid bacteria, with potential applications as biopreservatives. We describe here production purification and characterization of novel Lactobacillus pentosus for further properties on enhancement of food safety and shelf life of food products. LC/MS analysis techniques for the quantitative profiling of bacteriocins present in the probiotic preparations of Lactobacillus pentosus. LC-MS/MS analysis techniques, data analysis is novel in bacteriocin research and suitable for the comprehensive bioanalysis of diverse, low-abundant bacteriocins in complex sample.